2016
DOI: 10.3174/ajnr.a4864
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Antiplatelet Medication in Endovascular Treatment of Intracranial Aneurysms: Low-Dose Prasugrel versus Clopidogrel

Abstract: The prasugrel group showed more effective and consistent platelet inhibition. We may omit the antiplatelet response assay with the low-dose prasugrel premedication before the endovascular treatment of patients with unruptured aneurysms. Further study is required to determine whether there is benefit of this strategy regarding clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 29 publications
0
29
0
1
Order By: Relevance
“…Seven studies reported outcomes of patients undergoing neuroendovascular procedures managed on clopidogrel therapy compared with prasugrel therapy. 16,[22][23][24][25][26][27] Overall, prasugrel therapy in clopidogrel hyporesponders was associated with a similar rate of thrombotic complications compared with clopidogrel use in responders, with two of the seven comparative studies reporting a statistically significant decrease in thromboembolic complications. 26,27 Prasugrel also appeared to have similar rates of hemorrhagic complications, although one study 22 reported a higher rate of hemorrhagic complications compared with clopidogrel (19.4% vs 3.6%, p=0.02) in a heterogeneous population undergoing neuroendovascular procedures including stentassisted coiling (34.9%), aneurysm coiling (25.6%), PED placement (18.6%), extra-or intracranial carotid angioplasty and stenting (12.8%), onyx embolization (7%), and dural arteriovenous fistula coil embolization (1.2%).…”
Section: Prasugrelmentioning
confidence: 95%
See 1 more Smart Citation
“…Seven studies reported outcomes of patients undergoing neuroendovascular procedures managed on clopidogrel therapy compared with prasugrel therapy. 16,[22][23][24][25][26][27] Overall, prasugrel therapy in clopidogrel hyporesponders was associated with a similar rate of thrombotic complications compared with clopidogrel use in responders, with two of the seven comparative studies reporting a statistically significant decrease in thromboembolic complications. 26,27 Prasugrel also appeared to have similar rates of hemorrhagic complications, although one study 22 reported a higher rate of hemorrhagic complications compared with clopidogrel (19.4% vs 3.6%, p=0.02) in a heterogeneous population undergoing neuroendovascular procedures including stentassisted coiling (34.9%), aneurysm coiling (25.6%), PED placement (18.6%), extra-or intracranial carotid angioplasty and stenting (12.8%), onyx embolization (7%), and dural arteriovenous fistula coil embolization (1.2%).…”
Section: Prasugrelmentioning
confidence: 95%
“…Loading doses ranged from 20–60 mg, and maintenance doses ranged from 5–10 mg/day. Seven studies reported outcomes of patients undergoing neuroendovascular procedures managed on clopidogrel therapy compared with prasugrel therapy . Overall, prasugrel therapy in clopidogrel hyporesponders was associated with a similar rate of thrombotic complications compared with clopidogrel use in responders, with two of the seven comparative studies reporting a statistically significant decrease in thromboembolic complications .…”
Section: Options For Periprocedural Antiplatelet Therapymentioning
confidence: 99%
“…Overall, 682 unruptured aneurysms were treated endovascularly using PS (cases), whereas 672 unruptured aneurysms were treated endovascularly using CP (controls). Five studies compared treatment-related outcomes between the PS and the CP groups, [7][8][9][10]14 whereas 2 studies reported series of patients exclusively treated with PS. 12,13…”
Section: Literature Reviewmentioning
confidence: 99%
“…In 4 studies, 8,13,14 the loading dose of PS was 20 mg 1 day before treatment; in one study 9 it was 30 mg 1 day before treatment; in 2 studies, 10,12 the loading dose was between 40 and 60 mg 1 day before treatment; and in 1 study, 7 60 mg of PS was associated with 325 mg of acetylsalicylic acid (ASA). In 3 studies, CP, 75 mg, was combined with ASA, 100 mg 7,9 or ASA, 325 mg 10 , 5 days before treatment, whereas CP, 300 mg, was used alone in 2 studies 8,14 5 days before the procedure.…”
Section: Patient Population and Aneurysm Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation